2018
DOI: 10.1038/s41467-018-02854-4
|View full text |Cite|
|
Sign up to set email alerts
|

Strong indirect coupling between graphene-based mechanical resonators via a phonon cavity

Abstract: Mechanical resonators are promising systems for storing and manipulating information. To transfer information between mechanical modes, either direct coupling or an interface between these modes is needed. In previous works, strong coupling between different modes in a single mechanical resonator and direct interaction between neighboring mechanical resonators have been demonstrated. However, coupling between distant mechanical resonators, which is a crucial request for long-distance classical and quantum info… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 36 publications
(36 reference statements)
0
65
1
Order By: Relevance
“…All measurements were carried out in a dilution refrigerator at a base temperature of ~ 10 mK and a pressure below 10 −7 Torr. This structure was used to realize indirect coupling between 4 / 21 spatially-separated mechanical resonators, mediated with a phonon cavity 13 . Here we employ such kind of structure to explore coherent phonon dynamics in spatially-separated mechanical resonators.…”
Section: Sample Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…All measurements were carried out in a dilution refrigerator at a base temperature of ~ 10 mK and a pressure below 10 −7 Torr. This structure was used to realize indirect coupling between 4 / 21 spatially-separated mechanical resonators, mediated with a phonon cavity 13 . Here we employ such kind of structure to explore coherent phonon dynamics in spatially-separated mechanical resonators.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Since both 1 and 3 are neighbouring to 2 , avoided level crossing between 1 and 3 mediated by 2 is observed, which can be translated to an effective coupling between the non-neighbouring resonators ( 1 and 3 ). The indirect coupling strength 13 2 ⁄ between the spatially-separated resonators 1 and 3 is shown in Fig. 1e.…”
Section: Strongly-coupled Mechanical Resonatorsmentioning
confidence: 99%
“…The quasi-1D h-BN waveguide demonstrated here exhibits a prominently higher first band frequency (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and wider bandgap opening (3 MHz), compared to its counterparts made from conventional materials, such as silicon nitride (Si3N4), with similar geometry design ( Supporting Table S1) [35,36]. These favorable properties for high frequency (3-30 MHz) RF applications originate from the high Young's modulus and low mass density of h-BN, which bestow enhancement in mode-coupling nonlinearity of the resonators as well [29,30].…”
mentioning
confidence: 81%
“…In parallel with photonic components, such as photonic crystal cavities and optical resonators, which have been preliminarily demonstrated in h-BN crystals [13,14], phononic wave devices also play crucial roles in such hybrid schemes. Traveling at significantly slower speeds than the luminal speed of photons, phonons-the quanta of mechanical vibrations-have been suggested as better carriers allowing information to be stored, filtered and delayed over comparatively small length-scales but with high fidelity [15,16,17]. It has been widely demonstrated that mechanical motion can mediate energy/information transduction among different physical domains, as well as bridge the classical and quantum regimes.…”
mentioning
confidence: 99%
See 1 more Smart Citation